Gestión administrativa y su influencia en la calidad del servicio de la empresa pública municipal Terminal Terrestre del cantón Quevedo, año 2023 - Aguilar Antón, Arianna Leonela (2025)
The research project entitled Administrative management and its influence on the quality of service of the Empresa Pública Municipal Terminal Terrestre del Cantón Quevedo, Year 2023, aims to analyse the impact of administrative management on the quality of service offered in this terrestrial terminal. The methodology used was a mixed approach, combining qualitative and quantitative techniques. Structured surveys were carried out with 380 users and 10 terminal employees, as well as interviews with 3 managers. The study adopted an exploratory and descriptive design to obtain a comprehensive diagnosis of the administrative situation. Surveys of users and employees, as well as interviews with managers